Literacy experiences in the families of Turkish- and Russian- speaking kindergarten children - Kuyumcu, Reyhan; Senyldiz, Anastasia (Swiss Journal of Educational Research, 2018)
Preschool children with migration background experience different language and educational environments within their homes. These contexts are influenced by both the social situations and the cultural origins of the families. For example, the importance of oral and written language varies considerably between cultures. This article examines the impact of cultural characteristics of different homelands on the educational experiences of preschool children from immigrant families in Germany. Using data from two qualitatitive research projects, literacy practices of six Turkish- and Russian-speaking families are described and compared. The results indicate that family literacy practices can only partially be explained by the socioeconomic status and are determined by the cultural origins and other individual and family characteristics, as well. The article concludes by outlining some approaches to a culturally adaptive language education used by two preschool education programs.